Implementation of poka-yoke to achieve zero defects in an assembly line of a limited company. (1st January 2013) - Rajendra, G.; Suprabha, R.; Mahesha, C.R.
This paper aims at achieving zero defects in a starter assembly line by the implementation of poka-yoke technique. The study of the operations of starter assembly line with the help of cause and effect diagram revealed that there was a problem in stop ring and retainer assembly station. Then poka-yoke is implemented for correct sequence and complete pressing operation of stop ring and retainer assembly. With the implementation of poka-yoke, no defects were produced in the starter assembly line. No manual intervention was needed in the assembly. A good process quality was achieved. A check for effectiveness was done for a sample of 500 pieces and in all the samples complete pressing of the retainer and stop ring assembly was achieved. All the components were found to be good in the performance test. Finally, after implementation manpower was saved of 50% and cost was saved up-to 25%.